Preschool children’s negative affect and social skills in China: The moderating effect of the teacher–child relationship - Wang, Yingjie; Tao, Ying; Zhu, Li; Li, Yan; Huang, Dingwen (Frontiers in Psychology, 2022)
Negative affect is an important temperament in children, influencing their social skills. However, the evidence for this association in preschool children is limited. Moreover, the underlying mechanisms that explain the relationship between preschool children’s negative affect and social skills remain little understood. Thus, the primary goal of this study was to examine the moderating role of the teacher–child relationship in the associations between negative affect and social skills of Chinese preschoolers. A sample of 198 preschool children (Mage = 58.64 ± 3.83 months, 53% boys), recruited from 13 classes in two public kindergartens in Shanghai, China, participated in this one-year longitudinal study. The mothers reported children’s negative affect, while the teachers reported children’s social skills and the teacher–child relationship. Results of a series of moderating effect analyses showed that (1) T1 negative affect could significantly negatively predict T2 social skills (cooperation, self-control, and assertion), and (2) the associations between negative affect and social skills were moderated by the teacher–child relationship (including teacher–child closeness and conflict). Specifically, a high level of teacher–child closeness buffered the prediction of negative affect on social skills, while a high level of teacher–child conflict aggravated the said prediction. The findings highlight the importance of the teacher–child relationship in the development of children’s social skills during preschool age, when they have a high level of negative affect. This has important implications for the development of interventions to improve teacher–child relationships and children’s social skills.